2017
DOI: 10.1177/1403494817746535
|View full text |Cite
|
Sign up to set email alerts
|

A three-year national follow-up study on the development of community-level cancer rehabilitation in Denmark

Abstract: This study, which highlights improvements in the provision of community-level cancer rehabilitation, recommends that more effort be made to ensure equality in utilisation across patient groups, improved integration of municipal-level services into cancer care trajectories, more uniform documentation of service delivery and the enforcement of patient outcomes to gradually build a more robust evidence base for community-level cancer rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…A recent multi-institutional study concluded that HNC patients prefer multiple modes of information delivery (72%), with one-to-one consultation being the most preferred method for cancer education followed by internet-based interventions [38]. Our findings are also in line with a national study concerning cancer rehabilitation in Denmark, which concluded that there is a need for more well-validated documentation based on patient needs [43].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A recent multi-institutional study concluded that HNC patients prefer multiple modes of information delivery (72%), with one-to-one consultation being the most preferred method for cancer education followed by internet-based interventions [38]. Our findings are also in line with a national study concerning cancer rehabilitation in Denmark, which concluded that there is a need for more well-validated documentation based on patient needs [43].…”
Section: Discussionsupporting
confidence: 86%
“…Rehabilitation responsibilities at various authorities and on different governmental levels reported as a factor that can cause dissatisfaction, confusion or lower the trust of patients, as the allocation of responsibilities and authority is not always transparent. The municipalities do not posse specialized proficiency needed to elaborate rehabilitation of HNC patients, due to differences in population size and therefore to number of cancer incidence [43]. Both knowledge and professional skills are divided across great distances, which often hinders closer collaboration across professional groups and united specialized knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…However, ongoing monitoring and behavioral change support by a cancer exercise professional for those opting for generic activities are essential for success. Currently, there are more than 20 publications describing the implementation and, in many cases, the evaluation of community‐based programs for patients with cancer and survivors in North America, Australia, and Northern Europe . Below, we describe the largest programs in the United Kingdom and the United States, respectively.…”
Section: Types Of Programmingmentioning
confidence: 99%
“…Literature confirms that there exist key challenges for the delivery of services between municipalities; inadequate referral and recruitment procedures; lack of needs assessment tools; obstacles to ensuring collaboration and referral of patients between hospitals and municipalities; and inadequate evidence on the rehabilitation’s effect (Kristiansen et al, ; Kristiansen, Adamsen, Brinkmann, Krasnik, & Hendriksen, ). Future research should target interventions, for example education and training (Bartolo, et al, ) assisting interdisciplinary HCTs to provide best clinical practice based on evidence.…”
Section: Resultsmentioning
confidence: 99%
“…Betts et al found that clinical specialists encountered lifelong learning by taking on new responsibilities and may seek to close knowledge gaps (Betts, O'Donoghue, Aikin, Kelly, & Boudewyns, 2016) in efforts to keep their competences at an "updated level". Literature confirms that there exist key challenges for the delivery of services between municipalities; inadequate referral and recruitment procedures; lack of needs assessment tools; obstacles to ensuring collaboration and referral of patients between hospitals and municipalities; and inadequate evidence on the rehabilitation's effect (Kristiansen et al, 2017;Kristiansen, Adamsen, Brinkmann, Krasnik, & Hendriksen, 2015). Future research should target interventions, for example education and training assisting interdisciplinary HCTs to provide best clinical practice based on evidence.…”
Section: Organisation and Education And Training Of Hctsmentioning
confidence: 99%